2012
DOI: 10.1590/s0103-64402012000600008
|View full text |Cite
|
Sign up to set email alerts
|

Marginal adaptation of indirect restorations using different resin coating protocols

Abstract: This study evaluated the influence of material combinations used in the resin coating technique (RCT) on the marginal adaptation of indirect restorations with gingival margins in enamel (EM) and cement (CM). Eighty third-molars were used. Two cavities were prepared in each tooth. The cavities were distributed into 16 groups. Cavities with EM were filled with the following material combinations: G1: Single-Bond 2 (Sb2), G2: Sb2 + Bond/Scotchbond-Multipurpose (Sb2B), G3: Sb2 + Filtek-Flow Z350 (Sb2Fl), G4: Scotc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“… An opaque resin for masking discolored resin reduced the bond strength. Medina et al 2012 99 In vitro Marginal adaptation Evaluated the effect of different material combinations used in the resin coating technique (Single Bond 2/Sigle Bond 2+Scotch Bond Multi-Purpose/Sigle Bond 2+Filtek Flow/Scotch Bond Multi-Purpose/Clearfil S3/Clearfil S3+Bond Clearfil SE Bond/Clearfil S3+Protect Liner F/Clearfil SE Bond+ Protect Liner F) on the marginal adaptation of indirect restorations with gingival margins in enamel and cement. The most appropriate resin coating combinations were the groups that used a liner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… An opaque resin for masking discolored resin reduced the bond strength. Medina et al 2012 99 In vitro Marginal adaptation Evaluated the effect of different material combinations used in the resin coating technique (Single Bond 2/Sigle Bond 2+Scotch Bond Multi-Purpose/Sigle Bond 2+Filtek Flow/Scotch Bond Multi-Purpose/Clearfil S3/Clearfil S3+Bond Clearfil SE Bond/Clearfil S3+Protect Liner F/Clearfil SE Bond+ Protect Liner F) on the marginal adaptation of indirect restorations with gingival margins in enamel and cement. The most appropriate resin coating combinations were the groups that used a liner.…”
Section: Resultsmentioning
confidence: 99%
“…[92][93][94] Duarte et al 3 demonstrated that even if IDS favored bond strength, micro-leakage was not improved. Conversely, several studies have shown that if the DBA is combined with an LVR, a smaller gap formation in the dentin-restoration interface is observed, 31,[95][96][97][98][99] even if subjected to loading. 95,100 A variant of IDS undertaken in the access cavity of teeth subjected to endodontic treatment (immediate endodontic sealing) has been shown to reduce coronal leakage, which is the major cause of failure.…”
Section: Microleakage/adaptation Of the Final Restorationmentioning
confidence: 99%
“…All the teeth were thermocycled for 2,000 thermal cycles between water baths at 5 °C and 55 °C with a 30-s dwell time, according to previous studies [ 24–26 ]. Then, the teeth were coated with two layers of nail polish (Vinyl shine nail polish; Rimmel London, London, UK), except for a 2.0-mm rim around the restoration, to allow contact of the leakage-tracing agent with the margins of the restoration.…”
Section: Methodsmentioning
confidence: 99%
“…Another IDS technique was developed in which a sealing film is applied to the dentin surface immediately after tooth preparation using an adhesive system and a low-viscosity composite resin. [56] It is believed that this layer of low-viscosity composite resin isolates the underlying hybrid layer and consequently, aids in preserving the dentin seal. [7] Therefore, IDS techniques are based on the principle that adhesive systems bond better to freshly prepared dentin,[12] thus protecting the dentin – pulp complex and preventing or decreasing sensitivity and bacterial leakage during the provisional stage.…”
Section: Introductionmentioning
confidence: 99%